A basic methodology and plan orientation for evaluation of research and development organizations in Vietnam - Ngoc, Tran Hau; Thao, Pham Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Actually, the evaluation of research and development (R&D) organizations to serve the planning and re-structuring of the system of science and technology (S&T) organizations in Vietnam becomes an urgent need. Therefore, the authors of this paper want to share their points of view on the orientations of evaluation works of R&D organizations in Vietnam. The paper provides an approach to the problem through summarizing main contents on methodology for evaluation of R&D organizations (including: necessity of evaluation works; objectives of evaluation works; indicators, methods and procedure of evaluation works) and interprets necessary works, demands of resources and global plans for implementation which target a periodic practice of evaluation works. Code: 16080202<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">